Growth and Poverty in Africa: Shifting Fortunes and New Perspectives - Abebe Shimeles (Institute for the Study of Labor (IZA), 2014)
Growth has been high and widespread in the last decade in Africa. Whether this shift in Africa's fortune has impacted poverty has been a subject of controversy. This paper brings into focus recent evidence on the pace of poverty reduction in Africa and addresses whether or not previously held belief that Africa is too poor to grow is relevant today. The findings suggest that there is credible evidence for poverty to have declined significantly since the 1990s but at a lesser speed than growth in per capita GDP. More importantly, global poverty tends to respond much more strongly to shifts in sector of employment, particularly to increase in employment in the industrial sector, than to increase in mean income. In Africa the co-existence of a large traditional and informal sector with a dynamic modern sector will continue to pose a challenge for achieving a sustained reduction in poverty. Challenges of structural transformation and its attendant benefits are discussed using emerging thinking on industrial policies to achieve inclusive growth in Africa.
Keywords: O12; 330; economic growth; poverty traps; multidimensional poverty; structural transformation